A study on the efficacy and duration of the gow-gates mandibular block technique - Escoto, Elmer Jesus T.
Pain control is important in doing most dental procedures. When the procedure involves the lower jaw, an effective mandibular block of considerable duration, that is easy to administer, is needed. Volunteers were subjected to the Gow-Gates mandibular block technique. The effectivity and duration were tested be probing and extraction. Results showed that this technique is effective and of considerable duration but some mastery of this technique is required.